Estimates of RelSeq, Mesh1, and SAHMex Hydrolysis of (p)ppGpp and (p)ppApp by Thin Layer Chromatography and NADP/NADH Coupled Assays - Potrykus, Katarzyna; Thomas, Nathan E.; Bruhn-Olszewska, Bożena; Sobala, Michał; Dylewski, Maciej; James, Tamara; Cashel, Michael (Frontiers in Microbiology, 2020)
The Mesh1 class of hydrolases found in bacteria, metazoans and humans was discovered as able to cleave an intact pyrophosphate residue esterified on the 3’hydroxyl of (p)ppGpp in a Mn2+ dependent reaction. Here, thin layer chromatography (TLC) qualitative evidence is presented indicating the substrate specificity of Mesh1 from Drosophila melanogaster and human MESH1 also extends to the (p)ppApp purine analogs. More importantly, we developed real time enzymatic assays, coupling ppNpp hydrolysis to NADH oxidation and pppNpp hydrolysis to NADP+ reduction, which facilitate estimation of kinetic constants. Furthermore, by using this assay technique we confirmed TLC observations and also revealed that purified small alarmone hydrolase (SAH) from Methylobacterium extorquens displays a strong hydrolase activity towards (p)ppApp but only negligible activity towards (p)ppGpp. In contrast, the substrate specificity of the hydrolase present in catalytically active N-terminal half of the RSH protein from Streptococcus equisimilis (RelSeq) includes (p)ppGpp but not (p)ppApp. It is noteworthy that the RSH protein from M. extorquens (RSHMex) has been recently shown to synthesize both (p)ppApp and (p)ppGpp.